ANALISIS PENGAWASAN PENGELUARAN BARANG PADA TOKO BEBAS BEA DALAM KOTA (DUTY FREE SHOP) DALAM UPAYA MENGAMANKAN PENERIMAAN PAJAK DI KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN A JAKARTA - Pebriana Arimbhi; Edy Edy; Gandri Narandu (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
A Thesis discussed supervision to their expense of goods on one of the tweeps facilities the store is free the duties is under office customs jakarta, namely pt sj indonesia / lotte duty free in a bid to secure tax revenue.The purpose of he did this study is to find a monitoring system to their expense goods applied to PT SJ Indonesia / Lotte Duty Free in an effort to tax revenues and the obstacles with respect to the supervision. The research is based on the qualitative research descriptive by applying a technique the collection of data in the form of the objective of the interview and secondary data .The results of the interviews and the data on after that it is processed and analyzed in order to understand the supervision to their expense of goods which will be applied is he would do to PT SJ Indonesia / Lotte Duty Free in a bid to secure the country tax receipts. The result of this research, the author concluded that the supervision to their expense goods applied to PT SJ Indonesia / Lotte Duty Free in a bid to secure tax revenue has been running in accordance with the rules applied apply. But, its implementation happened obstacles is internal, like a coordination between supervision office, and obstacles which are external, as an opportunity used company related for committing a foul and have not the construction of a technological system and information centralized.